1999
DOI: 10.21273/jashs.124.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Green Mold Decay in Grapefruit with Postharvest Jasmonate Application

Abstract: Jasmonic acid (JA) and methyl jasmonate (MJ), collectively referred to as jasmonates, are naturally occurring plant growth regulators involved in various aspects of plant development and responses to biotic and abiotic stresses. In this study, we found that postharvest application of jasmonates reduced decay caused by the green mold Penicillium digitatum (Pers.: Fr.) Sacc. after either natural or artificial inoculation of grapefruit (Citrus paradisi Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 26 publications
2
49
1
1
Order By: Relevance
“…Our results showed that MeJA at all tested concentrations could not suppress the spore germination of P. expansum. This is similar with other research results which indicated that MeJA could not directly influence the growth of some fungal pathogens such as B. cinerea, P. digitatum and M. fructicola (Darras, Terry, & Joyce, 2005;Droby et al, 1999;Tsao & Zhou, 2000;Yao & Tian, 2005a). These results suggest that MeJA controls the postharvest blue mold decay and enhances the biocontrol efficacy of R. glutinis by mechanisms other than directly effecting pathogen growth/germination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that MeJA at all tested concentrations could not suppress the spore germination of P. expansum. This is similar with other research results which indicated that MeJA could not directly influence the growth of some fungal pathogens such as B. cinerea, P. digitatum and M. fructicola (Darras, Terry, & Joyce, 2005;Droby et al, 1999;Tsao & Zhou, 2000;Yao & Tian, 2005a). These results suggest that MeJA controls the postharvest blue mold decay and enhances the biocontrol efficacy of R. glutinis by mechanisms other than directly effecting pathogen growth/germination.…”
Section: Discussionsupporting
confidence: 91%
“…Exogenous application of methyl jasmonate (MeJA) has been considered as effective at inducing secondary metabolites in plant cell cultures, resulting in the expression of a set of defence genes and inducing resistance of host against pathogens (Epple, Apel, & Bohlmann, 1997;Kozlowski, Buchala, & Métraux, 1999). Recently, MeJA had shown promise in preventing postharvest disease and disorders in horticultural crops, application of MeJA has been reported to effectively suppress gray mold rot caused by Botrytis cinerea in strawberry (Moline, Buta, Saftner, & Maas, 1997), to decrease green mold decay caused by Penicillium digitatum in grapefruit (Droby et al, 1999), to reduce microbial contamination of freshcut celery and peppers (Buta & Moline, 1998), to decreased fruit decay infected by Colletotrichum gleosporioides and Alternaria alternata on papaya fruit (González-Aguilar, Buta, & Wang, 2003), to suppress anthracnose rot caused by Colletotrichum coccodes in tomato fruit (Tzortzakis, 2007), to reduce anthracnose rot caused by Colletotrichum acutatum infection in loquat fruit (Cao et al, 2008), and to inhibit brown rot caused by Monilinia fructicola in sweet cherry fruit (Yao & Tian, 2005a). Furthermore, exogenous application of MeJA has been found to enhance the efficacy of the antagonistic yeast Cryptococcus laurentii to control brown rot and blue mould caused by Monilinia fructicola and Penicillium expansum in peach fruit (Yao & Tian, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Droby et al (1999) performed in vitro experiments and indicated that neither JA nor MeJA had any direct antifungal effect on Penicillium digitatum spore germination or germ-tube elongation. Their results suggested that jasmonates probably reduced green-mold decay in grapefruit indirectly by enhancing the natural resistance of the fruit to P. digitatum.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial properties of EOs derived from many plant organs have been empirically recognised for centuries, although scientific confirmation has been reviewed recently (Burt, 2004). Methyl jasmonate has been shown to suppress fungal growth in grapefruit (Droby et al, 1999), reduce decay and maintain postharvest quality of papayas (González-Aguilar, Buta, & Wang, 2003), and inhibit microbial contamination of fresh-cut celery and peppers (Buta & Moline, 1998). It was also shown that blue mould (Penicillium expansum) in pears was controlled by allyl isothiocyanate vapour treatment (Mari, Leoni, & Cembali, 2002).…”
Section: Introductionmentioning
confidence: 99%